A New Trick for an Old Dog: L-Epinephrine Delivered Continuously in the Vapor Phase. (28th September 2021) - Winter, Meredith C.; Newth, Christopher J. L.; Castro, Cristina; Hotz, Justin C.; Ross, Patrick A.
Abstract : OBJECTIVES: Inhaled L-epinephrine is a known treatment of severe croup and postextubation upper airway obstruction. L-epinephrine can be delivered continuously in the vapor phase, but the indications, safety, and efficacy of this novel practice have yet to be evaluated. Theoretical risks are tachycardia, hypertension, and dysrhythmias. The study objective was to describe patient characteristics and vital sign changes related to continuous vaporized L-epinephrine use in critically ill children with the hypothesis that it can be practically and safely administered to children with subglottic edema and lower airway obstruction. DESIGN: Retrospective cohort study. SETTING: PICU and cardiothoracic ICU in a tertiary academic children's hospital. PATIENTS: Patients age 0–21 years treated with continuous vaporized L-epinephrine from 2013 to 2019. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Continuous vaporized L-epinephrine was administered 140 times to 129 subjects via a high-flow nasal oxygen device. The median age was 10.6 months (1.3; interquartile range, 4.8–17.1 mo). The most common indications were lower respiratory tract obstruction (45%), postextubation subglottic edema (31%), and croup (16%). Eighty-eight percent had no escalation of respiratory support within 24 hours of initiation of continuous vaporized L-epinephrine, 5% progressed to require endotracheal intubation, and 3% were reintubated within 24 hours of initiation of continuous vaporized L-epinephrine following an extubation attempt. After starting continuous vaporized L-epinephrine, 85% of subjects had a decrease in heart rate and 80% had a decrease in respiratory rate. Six subjects had an increase in heart rate, and eight had an increase in blood pressure of more than 20% from baseline. These subjects did not receive interventions specific to these vital sign changes, including discontinuation of continuous vaporized L-epinephrine. CONCLUSIONS: Continuous vaporized L-epinephrine was safely administered to critically ill children with most subjects demonstrating a decrease in heart rate, blood pressure, and respiratory rate.